Chinese FDI in Ethiopia : A World Bank Survey - World Bank (World Bank, Washington, DC, 2017)
Chinese Foreign Direct Investment (FDI) into Africa is on the rise and Ethiopia is at the forefront of this trend. On request of the Government, the World Bank surveyed 69 Chinese enterprises doing business in Ethiopia with a 95-question survey in May/June 2012. The survey covered various aspects of the foreign direct investment climate in Ethiopia, including infrastructure, sales and supplies, land, crime, competition, finance, human resources, and questions about general opportunities and constraints for doing business in Ethiopia. This report summarizes the results of survey and provides policy suggestions in light of the analysis; the report also provides some broader background of the expected benefits of FDI into Ethiopia as well as current policies and approaches to promote incoming investment. Addressing identified obstacles could help Ethiopia to take better advantage of foreign investors in order to accelerate the shift from a predominantly low-productivity agriculture-based economy towards a higher-productivity manufacturing and export-based economy. Experiences in successful countries around the world, and especially East Asia show that foreign investment is instrumental to facilitate such a structural transformation and to maintain sustained and broad-based economic development. This study recommends five main areas for policy adjustments to facilitate foreign investors coming into Ethiopia: adjust customs clearance procedures and trade regulations; facilitate currency convertibility and increase transparency of the exchange rate policy; improve tax administration consistency and efficacy; execute impartial labor regulation; and increase the supply and quality of skilled workers.